Recensiones - Orduña Prada, Enrique; de la Fuente Cabero, Mª Inmaculada; Ballesteros Moffa, Luis Ángel; González-Varas Ibáñez, Santiago; Almeida Cerreda, Marcos; Oller Rubert, Marta; Martínez Bargueño, Manuel (Revista de Estudios de la Administración Local y Autonómica, 2011)